Phytopharmacological Evaluation of Different Solvent Extract/Fractions From Sphaeranthus indicus L. Flowers: From Traditional Therapies to Bioactive Compounds - Ahmad, Hafiz Ibtesam; Nadeem, Muhammad Faisal; Shoaib Khan, Haji Muhammad; Sarfraz, Muhammad; Saleem, Hammad; Khurshid, Umair; Locatelli, Marcello; Ashraf, Muhammad; Akhtar, Naveed; Zainal Abidin, Syafiq Asnawi; Alghamdi, Adel (Frontiers in Pharmacology, 2021)
Sphaeranthus indicus L. is a medicinal herb having widespread traditional uses for treating common ailments. The present research work is aimed to explore the in-depth phytochemical composition and in vitro reactivity of six different polarity solvents (methanol, n-hexane, benzene, chloroform, ethyl acetate, and n-butanol) extracts/fractions of S. indicus flowers. The phytochemical composition was accomplished by determining total bioactive contents, HPLC-PDA polyphenolic quantification, and UHPLC-MS secondary metabolomics. The reactivity of the phenolic compounds was tested through the following biochemical assays: antioxidant (DPPH, ABTS, FRAR, CUPRAC, phosphomolybdenum, and metal chelation) and enzyme inhibition (AChE, BChE, α-glucosidase, α-amylase, urease, and tyrosinase) assays were performed. The methanol extract showed the highest values for phenolic (94.07 mg GAE/g extract) and flavonoid (78.7 mg QE/g extract) contents and was also most active for α-glucosidase inhibition as well as radical scavenging and reducing power potential. HPLC-PDA analysis quantified the rutin, naringenin, chlorogenic acid, 3-OH benzoic acid, gallic acid, and epicatechin in a significant amount. UHPLC-MS analysis of methanol and ethyl acetate extracts revealed the presence of well-known phytocompounds; most of these were phenolic, flavonoid, and glycoside derivatives. The ethyl acetate fraction exhibited the highest inhibition against tyrosinase and urease, while the n-hexane fraction was most active for α-amylase. Moreover, PCA analysis highlighted the positive correlation between bioactive compounds and the tested extracts. Overall, S. indicus flowers extracts were found to contain important phytochemicals, hence could be further explored to discover novel bioactive compounds that could be a valid starting point for future pharmaceutical and nutraceuticals applications.